Analisis Fashal Dalam Q.S. Al-Mulk Ayat 19 Studi Tentang Kekuasaan Allah - Fadwa Nabilah; Bunayya Zean Fathir; Nursumayyah Damanik (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Not everyone is able to understand the messages in the Al-Quran. So in an effort to understand it, fashal is an important part that must be studied to avoid confusion in the meaning of the verses of the Koran that are addressed to humans. Fashal is usually used to separate sentences that have various forms. The aim of this research is to describe the meaning of fashal, explain the division of various types of fashal and the function of fashal, and analyze the form of fashal in Q.S Al-Mulk verse 19. The method used in this research is a qualitative method with a library research approach. The data sources used in this research include primary and secondary data sources originating from books and journals as a relevant basis. The analysis used in this research is descriptive analysis which provides a broader explanation and is in a form that is easy to understand.